TIPICO XI: report of the first series and podcast on infectious diseases and vaccines (aTIPICO) - Federico Martinón-Torres; Adolfo García-Sastre; Andrew J. Pollard; Carlos Martín; Albert Osterhaus; Shamez N Ladhani; Octavio Ramilo; Jose Gómez Rial; Antonio Salas; F Xavier Bosch; María Martinón-Torres; Michael J. Mina; et al. (Taylor & Francis Group, 2021)
TIPiCO is an annual expert meeting and workshop on infectious diseases and vaccination. The edition of 2020 changed its name and format to aTIPiCO, the first series and podcasts on infectious diseases and vaccines. A total of 13 prestigious experts from different countries participated in this edition launched on the 26 November 2020. The state of the art of coronavirus disease-2019 (COVID-19) and the responsible pathogen, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), and the options to tackle the pandemic situation were discussed in light of the knowledge in November 2020. Despite COVID-19, the status of other infectious diseases, including influenza infections, respiratory syncytial virus disease, human papillomavirus infection, measles, pertussis, tuberculosis, meningococcal disease, and pneumococcal disease, were also addressed. The essential lessons that can be learned from these diseases and their vaccines to use in the COVID-19 pandemic were also commented with the experts.